Reproducibility of energy and macronutrient intake and related substrate oxidation rates in a buffet-type meal - Arvaniti, Konstantinia; Richard, Denis; Tremblay, Angelo (British journal of nutrition, 2000)
The aim of this present study was to determine the reliability of a buffet-type meal as a measure of spontaneous energy and macronutrient intake. In addition, we evaluated the short-term effects of diet on the composition of the substrate mix oxidized postprandially. Fourteen male subjects had ad libitum access to a variety of foods from a buffet-type meal offered in the laboratory during two identical sessions. The foods comprising the test meal had varying amounts of protein, lipid and carbohydrate. The results showed that there were significant intraclass correlations (ri) for energy (ri 0·97, P = 0·0001), lipid (ri 0·97, P = 0·0001), carbohydrate (ri 0·92, P = 0·0003) and protein (ri 0·82, P = 0·0072) intake between the two meal sessions. Hunger and fullness levels measured immediately before and during 4 h after the meal were identical under the two conditions. In addition, there was no significant difference between the two sessions for RQ and resting energy expenditure, which showed significant reproducibility for measurements obtained immediately before, immediately after, as well as 30 min after, the buffet. This present study demonstrates the high reproducibility of energy and macronutrient intake and oxidation rate values obtained with a buffet-type meal in healthy male subjects and suggests that the use of this test is a reliable method for assessment of macronutrient preferences in the laboratory.